Implicit Labor Contracts and Free Entry - Kihlstrom, Richard E.; Laffont, Jean-Jacques (Quarterly Journal of Economics, 1983)
The model investigated here is an adaptation of the free-entry model introduced in Kihlstrom-Laffont [1979]. In that model the only labor market is one in which employers pay workers an ex ante guaranteed wage. In the model of this paper, there is also a spot market for labor. In the earlier sections of the paper, the existence of the equilibrium is established, and its efficiency is investigated. In this analysis it is assumed that all individuals are identical. In the later sections we drop this assumption and investigate conditions under which employers are more risk-averse than workers.